The Correlation Study between TP53 Gene Expression and Acute Myeloid Leukemia in Iraq - Dawood, Hadeel Hameed; Mohammed , Rana Kadhim (Iraqi Journal of Science, 2023)
Acute myeloid leukemia represents the most prevalent type of acute leukemia in adults. Mutations in the tumor protein (TP53) gene have been found in more than half of all human cancers. This study was done to investigate the relationship between TP53 gene expression and the appearance and progression of acute myeloid leukemia in Iraq. This study included 100 subjects, divided into 60 patients suffering from pre-diagnostic acute myeloid leukemia and 40 healthy individuals. The difference in TP53 gene expression between acute myeloid leukemia patients and healthy individuals has been investigated, and the gene expression of TP53 has been measured after extraction of total RNA at concentrations (15–83 ng/µl) and purity (1.76-2). Gene expression has involved calculating the double ΔCt value to assess TP53 expression in the presence of the GAPDH gene as a reference gene. Results showed that gene expression folding (2-∆∆Ct) reflects significant differences in TP53 gene expression. There was overexpression (up-regulation) of the TP53 gene in acute myeloid leukemia patients (mean ± SD: 2.29±2.12) compared with controls (1 ± 0.43), with a p=0.04.